(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
The development of students’ writing skills is a complex and iterative process that requires continuous support and guidance. Among the various instructional strategies, feedback has been widely recognized as a crucial factor that significantly influences the quality and progression of student writing. This article examines the multifaceted role of feedback in enhancing students’ writing development by analyzing different types of feedback including teacher feedback, peer feedback, formative and summative feedback and their effects on learners’ writing performance. Drawing on an extensive review of recent empirical studies and theoretical perspectives, the paper explores how timely, specific, and constructive feedback fosters students’ ability to identify errors, reflect on their writing, and implement meaningful revisions. Furthermore, the emotional and motivational dimensions of feedback are considered, acknowledging that feedback not only informs but also encourages and empowers students to become autonomous writers. Challenges faced by educators, such as providing individualized feedback in large classrooms and balancing corrective and supportive comments, are also discussed. The article highlights the potential of integrating technological tools to complement traditional feedback methods, offering immediate and accessible responses. Overall, the findings emphasize that effective feedback is an indispensable component of writing instruction that contributes to learners’ academic success and lifelong writing competence.